THE EFFECT OF CASH FLOW AND NET PROFIT ON STOCK PRICES WITH DIVIDENDS AS INTERVENING VARIABLES IN ISLAMIC BANKING LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2018 – 2022 - Vina Adelia; Rahmi Syahriza; Aqwa Naser Daulay (RADJA PUBLIKA, 2024)
This study aims to determine the Effect of Cash Flow and Net Profit on Stock Prices Through Dividends in Islamic Banking Listed on the Indonesia Stock Exchange for the 2018-2022 Period. The type of research used in this study is Explanatory Research with a quantitative method . This study uses 60 research samples derived from panel data of Islamic banking companies listed on the Indonesia Stock Exchange from 2018 to 2022. Data processing in this study uses the help of Smart PLS, with the stages of analysis carried out in this study, namely the outer model including composite stability and cronbach alpha, then the inner model which includes: r-square (r2) and hypothesis testing with t-statistics and indirect effect tests. The results of Smart PLS in this study on the t-statistic test are Cash Flow has no effect on Stock Price, Net Income has an effect on Stock Price, Dividends have an effect on Stock Price, Cash Flow has no effect on Dividends, Net Income has an effect on Dividends, while the results of the path analysis show that Cash Flow has no effect on Stock Price Through Dividends, Net Income has an effect on Stock Price Through Dividends. This indicates that Dividends are a significant mediator in the relationship between Net Income and Stock Price, where higher net income increases dividends, which in turn can increase stock prices. While cash flow does not always reflect the overall performance of the company because its operations are based on sharia principles that avoid usury. Therefore, cash flow fluctuations may not have a significant effect on dividends or investor decisions in assessing stock prices.